Atlas Kriegsschadenskarten Deutschland : Stadtkartierung und Heritage Making im Wiederaufbau um 1945 - Enss, Carmen M. 1975- HerausgeberIn; Knauer, Birgit HerausgeberIn (De Gruyter, 2022)
For the first time, the Atlas Kriegsschadenskarten (Atlas of War Damage Maps) prepares an important source inventory for urban research and presents maps of Nuremberg, Hamburg, Hanover, Freiburg, Leipzig, and Essen from the 1940s and 1950s in large-format illustrations. Introductory essays are devoted to the development of war damage recording and discuss the significance of map documents for reconstruction and heritage processes